PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Cut Meutia Mustika Suri; Yohana Kartika; Masrian Fauzan; Arham Syaukani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
It is important to know the effect both jointly and partially between discipline and motivation on employee performance. This research uses quantitative methods with explanatory research using primary data and secondary data. The population in this study were employees at the Regional Company Offices of Pasar Kota Medan and as many as 82 employees were used as research samples. The data analysis technique used is multiple and partial linear regression using SPSS 24.0. The discipline variable is significant at 0.029, so it can be concluded that employee performance is influenced by discipline (hypothesis 1 is accepted). The motivation variable has a significant value at 0.013. So it can be concluded that motivation affects employee performance (hypothesis 2 is accepted). The work facility variable has a significant value at 0.016. So it can be concluded that work facilities have an effect on employee performance (hypothesis 3 is accepted). The results showed that the discipline variables and work motivation together had a positive effect on employee performance. This is evidenced by the statistical results of the regression test which obtained a probability value of 0.000 smaller than α (α = 0.05), it can be explained that discipline and work motivation have a positive effect on employee performance. Then the fourth hypothesis is accepted.